2019
DOI: 10.1186/s12978-019-0790-x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and family planning in Uttar Pradesh, India: major progress and persistent gaps

Abstract: Background Uttar Pradesh (UP) is the most populous state in India with historically high levels of fertility rates than the national average. Though fertility levels in UP declined considerably in recent decades, the current level is well above the government’s target of 2.1. Data and methods Fertility and family planning data obtained from the different rounds of Sample Registration System (SRS) and the National Family Health Survey (NFHS). We analyzed fertility and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…In one of the worst coverage divisions such as Basti, the demand met by modern contraception in urban areas is 60% compared to only 16% in rural areas. These above results are also corroborated by district level analysis of fertility decline by others [ 22 ]. The study has shown that the sterilization usage has increased substantially in very low and middle TFR clusters, while the contribution of the same method has declined, and traditional method has increased in high TFR cluster [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In one of the worst coverage divisions such as Basti, the demand met by modern contraception in urban areas is 60% compared to only 16% in rural areas. These above results are also corroborated by district level analysis of fertility decline by others [ 22 ]. The study has shown that the sterilization usage has increased substantially in very low and middle TFR clusters, while the contribution of the same method has declined, and traditional method has increased in high TFR cluster [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
“…These above results are also corroborated by district level analysis of fertility decline by others [ 22 ]. The study has shown that the sterilization usage has increased substantially in very low and middle TFR clusters, while the contribution of the same method has declined, and traditional method has increased in high TFR cluster [ 22 ]. According to the study, it is due to lack of availability and accessibility of preferred method of choice.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It has been established that reliance on traditional methods of contraception was associated with high failure rates which might result in subsequent unplanned pregnancies and abortions. 35 Using traditional methods put these women at risk of repeated abortions. Findings suggested a need for behavioural change among women towards adopting more effective Consistent with previous studies, education was found to have a positive relationship with the uptake of short-acting modern methods.…”
Section: Discussionmentioning
confidence: 99%